Effect of Feeding Prosopis juliﬂora Pods and Leaves on Performance and Carcass Characteristics of Afar Sheep - Ali, Ahmed Seid; Tudsri, Sayan; Rungmekarat, Sarawut; Kaewtrakulpong, Kriengki (Agriculture and Natural Resources, 2012)
Twenty Afar male sheep with initial mean body weight ± SD of 17.87 ± 1.19 kg were used to evaluate the effect of replacing commercial feed with Prosopis juliﬂora pods and leaves on growth performance, carcass and meat quality characteristics. Animals were equally divided into four dietary treatment groups for 120 d (Rhode grass hay (RGH), RGH + 300 g ground P. juliﬂ ora pods (PJP), RGH + 150 g each ground P. juliﬂ ora pods and leaves mix (PJPLM) and RGH + 300 g commercial concentrate mix (CCM) per head per day). Total dry matter and crude protein intakes increased (P < 0.05) in treatments supplemented with ground PJP and CCM. The average weight gain and meat quality parameters obtained by supplementing with 300 g ground PJP were signiﬁ cantly higher than the RGH and PJPLM treatment groups, but were comparable with that of CCM. The present study demonstrated the potential of using PJP for Afar lambs without adverse effects on growth and carcass characteristics. However, the intake of PJP reduced when mixed with leaves and this indicates the leaves are unpalatable.